Pengembangan Media Pembelajaran Puzzle Interaktif sebagai Media Pengenalan Keaksaraan Awal bagi Anak Usia Dini - Kirom, Sabitul; Rofiq, Arta Ainur (Jurnal Simki Pedagogia, 2024)
There are still many children who have not developed their early literacy skills. One of the factors causing this is that children's interest in learning is different. The purpose of this research is to develop an interactive puzzle as a medium for introducing early literacy. The puzzle media developed is interactive by adjusting the characteristics of child development. The research method uses R&D adopting the ADDIE model. Data collection techniques through observation and interviews. The puzzle media was tested with expert tests and field tests. The results of this study are interactive puzzle media declared valid based on expert validation and users. Interactive puzzles are effective in introducing early literacy. The practicality of this interactive puzzle is very good. It can be concluded that interactive puzzle media is effective, valid, and practical to be applied in the introduction of early literacy in children.